Maraknya Fenomena Hate Comment di Kalangan Remaja Indonesia dalam Bermedia Sosial - Zain, Abyan; Safa Mutiara, Ayu; Anggita Fitriyani, Jeanny; Cynthia, Agnes; Tarisa Sabrina, Fadiah; Falevi, Yunizar; Amelia, Sandra; Gilang Bhaswara, Nadhif; Setya Abrilrizky, Haryadian; Putri Eriana, Nadhifa; Dwiastuti, Winda; Syahrul Ramadhan, Muhammad; Subhandi Bakhtiar, Handar (Jurnal Hukum Statuta, 2023)
Abstract Apart from the many conveniences that are felt, of course there are also negative effects from the current rapid development of technology, the rise of hate comments that occur on social media is a form of the negative impact of current technological developments. This journal was created with the aim of studying the meaning of hate comments and researching the regulations in Indonesia that regulate hate comments, and to understand more about the impact of hate comments so that hate comments can be reduced. This study uses the literature study research method in which the author seeks data and information from various types of references such as documents, both written documents, documents in the form of photographs, documents in the form of images, and documents in electronic form that can be used as sources in research process. It can be concluded that hate speech is a word, deed, writing or action that can lead to acts of violence that demean the dignity of fellow human beings, resulting in stigma from those who commit or are called perpetrators or those who are victims of these actions. hate comments that are often carried out on social media are included in hate speech. Indonesia has several regulations governing hate comments including the ITE Law, the Criminal Code, and the Chief of Police Circular Number: SE/06/X/2015 concerning Handling Hate Speech. In addition, hate comments also have some bad effects for victims. as well as perpetrators. Keywords: Hate comment, Social Media, Hate Speech